2003
DOI: 10.1016/s0378-1097(03)00054-5
|View full text |Cite
|
Sign up to set email alerts
|

Novel pyrazine metabolites found in polymyxin biosynthesis byPaenibacillus polymyxa

Abstract: A complex mixture of methyl-branched alkyl-substituted pyrazines was found in the growth medium of the polymyxin-producing bacterium Paenibacillus polymyxa, and of these, seven are new natural compounds. A total of 19 pyrazine metabolites were identified. The dominant metabolite was 2,5-diisopropylpyrazine as identified using a combination of high-resolution mass spectrometry, (1)H- and (13)C-nuclear magnetic resonance, gas chromatography-mass spectrometry as well as co-elution with an authentic standard. Its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(66 citation statements)
references
References 18 publications
1
63
0
2
Order By: Relevance
“…Co-production of polymyxin E1 and a lantibiotic from P. polymyxa strain OSY-DF are potentially useful in food and medical applications [17]. P. polymyxa also produces pyrazine metabolites which was stimulated by valine supplementation [48]. In 2005, Stern et al [49] evaluated anti-Campylobacter activity of three P. polymyxa strains from poultry production environments.…”
Section: P Polymyxa As Antimicrobial Agentmentioning
confidence: 99%
“…Co-production of polymyxin E1 and a lantibiotic from P. polymyxa strain OSY-DF are potentially useful in food and medical applications [17]. P. polymyxa also produces pyrazine metabolites which was stimulated by valine supplementation [48]. In 2005, Stern et al [49] evaluated anti-Campylobacter activity of three P. polymyxa strains from poultry production environments.…”
Section: P Polymyxa As Antimicrobial Agentmentioning
confidence: 99%
“…The improved productions of other cyclic lipopeptide antibiotics with acyl side chains have previously been achieved by supplement of these amino acids or fatty acids. 5,6,7 Here, we report an improvement in the production ratio of TPPs by addition of the postulated precursors such as branched chain amino acids, short-chain carboxylic acids or 3-hydroxy fatty acids. Under the standard culture conditions, TPPs were produced in the ratio of TPPA (8.4%), TPPB (8.9%), TPPC (71.3%) and TPPD (11.4%).…”
Section: Introductionmentioning
confidence: 93%
“…The performed bioassays with the volatile compound 2,5-bis(1-methylethyl)-pyrazine revealed significant antibacterial and antifungal Exploring bacterial interspecific interactions for discovery of novel antimicrobial compounds 132 activity against the used microbial strains. Previous studies have already shown that pyrazine compounds can exhibit antimicrobial activities (Beck et al, 2003;Kucerova-Chlupacova et al, 2015). The detected pyrazine is most probably produced by the Burkholderia isolate, as small amounts of this compound were detected in the monoculture of these bacteria but not in monocultures of Paenibacillus.…”
Section: Discussionmentioning
confidence: 85%
“…The detected pyrazine is most probably produced by the Burkholderia isolate, as small amounts of this compound were detected in the monoculture of these bacteria but not in monocultures of Paenibacillus. The bacterial production of the volatile 2,5-bis(1-methylethyl)-pyrazine was ,so far, only reported for few bacteria (Beck et al, 2003;Dickschat et al, 2005;Rajini et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation